Aflatoxin B1: Challenges and Strategies for the Intestinal Microbiota and Intestinal Health of Monogastric Animals - Hyunjun Choi; Yesid Garavito-Duarte; Alexa R. Gormley; Sung Woo Kim (Toxins)
The objective of this review is to investigate the impacts of aflatoxins, particularly aflatoxin B1 (AFB1), on intestinal microbiota, intestinal health, and growth performance in monogastric animals, primarily chickens and pigs, as well as dietary interventions to mitigate these effects. Aflatoxin B1 contamination in feeds disrupts intestinal microbiota, induces immune responses and oxidative damage, increases antioxidant activity, and impairs jejunal cell viability, barrier function, and morphology in the small intestine. These changes compromise nutrient digestion and reduce growth performance in animals. The negative impact of AFB1 on the % change in average daily gain (ΔADG) of chickens and pigs was estimated based on meta-analysis: ΔADG (%)chicken = −0.13 × AFB1 intake per body weight (ng/g·d) and ΔADG (%)pig = −0.74 × AFB1 intake per body weight (µg/kg·d), indicating that increasing AFB1 contamination linearly reduces the growth of animals. To mitigate the harmful impacts of AFB1, various dietary strategies have been effective. Mycotoxin-detoxifying agents include mycotoxin-adsorbing agents, such as clay and yeast cell wall compounds, binding to AFB1 and mycotoxin-biotransforming agents, such as specific strains of Bacillus subtilis and mycotoxin-degrading enzyme, degrading AFB1 into non-toxic metabolites such as aflatoxin D1. Multiple mycotoxin-detoxifying agents are often combined and used together to improve the intestinal health and growth of chickens and pigs fed AFB1-contaminated feeds. In summary, AFB1 negatively impacts intestinal microbiota, induces immune responses and oxidative stress, disrupts intestinal morphology, and impairs nutrient digestion in the small intestine, leading to reduced growth performance. Supplementing multi-component mycotoxin-detoxifying agents in feeds could effectively adsorb and degrade AFB1 co-contaminated with other mycotoxins prior to its absorption in the small intestine, preventing its negative impacts on the intestinal health and growth performance of chickens and pigs.